COMPARATIVE ANALYSIS OF THE TREATMENT OF CERVICAL CANCER IIA-IIB STAGES: A RETROSPECTIVE CASE STUDY OF CONCURRENT CHEMORADIOTHERAPY (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
Efficacy and safety of concurrent chemoradiotherapy (CCRT) for patients with stage IIa-IIb cervical cancer were evaluated in this study. Stage IIa-IIb cervical cancer is defined by tumor invasion of the parametrium or the upper two-thirds of the vagina according to the 2018 FIGO staging system. Although CCRT is a widely used therapy for locally advanced cervical cancer, its use to stage IIa-IIb disease is still debatable. The purpose of the study was to contrast the clinical outcomes and side effects of CCRT with those of historical controls who underwent either radical surgery or radiotherapy (RT) alone.